Dynamical friction in slab geometries and accretion discs. Issue 4 (9th September 2019) - Vicente, Rodrigo; Cardoso, Vitor; Zilhão, Miguel
ABSTRACT: The evolution of planets, stars, and even galaxies is driven, to a large extent, by dynamical friction of gravitational origin. There is now a good understanding of the friction produced by extended media, either collisionless or fluid-like. However, the physics of accretion or protoplanetary discs, for instance, is described by slab-like geometries instead, compact in one spatial direction. Here, we find, for the first time, the gravitational wake due to a massive perturber moving through a slab-like medium, describing e.g. accretion discs with sharp transitions. We show that dynamical friction in such environments can be substantially reduced relatively to spatially extended profiles. Finally, we provide simple and accurate expressions for the gravitational drag force felt by the perturber, in both the subsonic and supersonic regime.